2010
DOI: 10.1186/1471-244x-10-52
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Posttraumatic Stress Disorder Among Deployed US Male Marines

Abstract: BackgroundCombat exposure has been reported as one of the strongest risk factors for postdeployment posttraumatic stress disorder (PTSD) among military service members. Determining the impact of specific deployment-related exposures on the risk of developing PTSD has not been fully explored. Our study objective was to explore the relationship between specific combat exposures and other life experiences with postdeployment PTSD.MethodsThis study consisted of male Marines who completed a Recruit Assessment Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 51 publications
6
87
0
Order By: Relevance
“…Across a number of studies, combat exposure has been linked with PTSD in a "dose response" manner, with greater severity of combat exposure associated with greater likelihood and greater severity of PTSD symptoms [34][35][36][37]. In a retrospective study, Iversen and colleagues (2008) found that combat-related experiences were the strongest predictor of PTSD in a sample of U.K. military personnel when evaluating demographic, predeployment, and deployment-related factors [34].…”
Section: Discussionmentioning
confidence: 99%
“…Across a number of studies, combat exposure has been linked with PTSD in a "dose response" manner, with greater severity of combat exposure associated with greater likelihood and greater severity of PTSD symptoms [34][35][36][37]. In a retrospective study, Iversen and colleagues (2008) found that combat-related experiences were the strongest predictor of PTSD in a sample of U.K. military personnel when evaluating demographic, predeployment, and deployment-related factors [34].…”
Section: Discussionmentioning
confidence: 99%
“…US studies have shown that in addition to injury on deployment, combat experiences [91,188], combat exposure [27,147], killing in war [27,121], witnessing dead bodies [90,137], discharging a weapon and deployment-related stressors [27] were related to adverse health conditions such as PTSD and alcohol problems. In addition to combat exposures, the fear of injury or death while on deployment has also been identified as an important risk factor for both PTSD symptoms and alcohol misuse [95,137,188].…”
Section: Combat Exposuresmentioning
confidence: 99%
“…Exposure to chemical, biological and other environmental factors continues to be a major non-combat concern in some military members deployed to the Middle East [137,165,171], although in some studies [86] the level of concern was low. It is important to note that ADF members may have been located in different areas in the MEAO and performed different tasks from US and UK defence forces, so findings about particular health conditions may not be applicable to Australian serving personnel.…”
Section: Environmental Exposuresmentioning
confidence: 99%
“…For example, for the item "I would recommend VETS PREVAIL to a friend dealing with combat or postdeployment stress," participants reported "strong" agreement (4.54 ± 0.89). Table 5 shows that depressed mood, as measured by the CES-D 10 in the intention-to-treat analysis, significantly declined from baseline (week 0) to week 4 and from baseline to week 12, but not from baseline to week 8 Table 5 shows that symptoms of posttraumatic stress in the intention-to-treat analysis significantly declined from baseline (week 0) to weeks 4, 8, and 12. A similar significance pattern occurred in the per-protocol and completer analyses.…”
Section: Feasibilitymentioning
confidence: 99%
“…Conversely, several common resiliency factors have been identified for these disorders in the same domains that are expected to be protective based on prior studies of mental disorders: behavioral (engagement in meaningful activities), cognitive (self-efficacy, problem-solving skills), and interpersonal relations (enhanced social support) [6][7]. However, negative affect can exacerbate both disorders, increasing functional impairment and worsening corespecific symptoms [8][9][10][11]. Without intervention, both disorders impair the individual's performance in work, military, and personal roles [5].…”
Section: Introductionmentioning
confidence: 99%